AN ANALYSIS ON STUDENTS’ ANXIETY FACTORS IN SPEAKING TEST - Gebi, Maura (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research aimed at discovering The Student’s Anxiety Factors in Speaking Test. The type of the research is descriptive quantitative, that was made to analyze the students’ anxiety in speaking test. The purposes of doing this research were to describe the levels of students’ anxiety, the sources of students’ anxiety and strategies that they used to decrease the anxiety when speaking. The technique of collecting data that was applied by the researcher was questionnaire (open and close questionnaire). It was found that most of the respondents have mildly anxious level of anxiety. Only a student has very relaxed level of anxiety. Factors of students’ anxiety come from learner beliefs about language learning, personal and interpersonal anxiety, and the instructor beliefs about language teaching. The main factor of students’ anxiety is learner’s belief. The strategies that were used by the students to reduce the feeling of anxiety are preparation, relaxation and positive thinking Keywords: Students’ Anxiety, Speaking Test, Anxiety Factors, Strategies Abstrak: Penelitian ini bertujuan untuk menemukan factor kecemasan siswa dalam tes berbicara. Tipe penelitian ini adalah kuantitatif deskriptif, yang dibuat untuk menganalisis kecemasan siswa dalam tes berbicara. Tujuan dari dilakukannya penelitian ini adalah untuk mendeskripsikan level kecemasan siswa, sumber kecemasan siswa dan strategi yang mereka gunakan untuk mengatasi kecemasan ketika berbicara. Tehnik pengambilan data yang dipakai peneliti adalah kuesioner (open dan close kuesioner). Penelitian ini menemukan hampir kebanyakan dari siswa berada pada level sangat rileks. Faktor kecemasan siswa berasal dari kepercayaan siswa terhadap proses pembelajaran, kecemasan personal dan interpesonal, dan kepercayaan instruktor dalam proses pengajaran. Strategi yang digunakan murid untuk mengurangi perasaan cemas adalah persiapan, relaksasi dan positif thinking. Kata Kunci: Kecemasan Siswa, Tes Berbicara, Faktor Kecemasan, Strategi